1183. A Prospective Epidemiological & Immunological Study of Cytomegalovirus infection in SLE Patients Receiving Immunosuppressant. (31st December 2020) - Autto, Suphanan; Pisitkun, Prapaporn; Apiwattanakul, Nopporn; Bruminhent, Jackrapong
Abstract: Background: Cytomegalovirus (CMV) infection has been emerging among autoimmune disease patients. CMV-specific cellular immunity has been shown to be correlated with CMV clearance in transplant recipients, however, this correlation has not been assessed in autoimmune disease patients. We aimed to investigate the epidemiology and clinical variables of CMV infection focused on CMV-specific cellular response of CMV infection in active systemic lupus erythematosus (SLE) patients receiving immunosuppressant. Methods: A prospective cohort study of active SLE patients who received immunosuppressant and underwent preemptively monitored for CMV infection by quantitative real-time PCR (Abbott RealTime CMV assay). Clinical variables were collected. CMV-specific cellular immune responses were measured by an enzyme-linked immunosorbent assay (QuantiFERON-CMV ® ) and intracellular cytokine assay. Clinically significant CMV infection was defined as CMV disease or plasma CMV DNA loads > 1, 000 IU/mL. Results: We included 45 active SLE patients in our cohort. Among 39 evaluable patients, there were 36 (92%) female patients with a median age of 28 (IQR 24-44) years. A median SLEDAI score was 16 (IQR 9-20). Seventy-four % had renal involvement. Methylprednisolone was the most common immunosuppressive regimen (94.9%). Thirty-six (92.3%) patients were CMV-seropositive. Clinically significant CMV infection occurred in 6 (25.6%) patients included asymptomatic CMV infection (79.3%), CMV syndrome (17.3%), and CMV tissue invasive disease (3.4%). Among 197 blood samplings, there were 16 (8.1%) episodes of clinically significant CMV infection. The distributions of QuantiFERON-CMV ® status were reactive, non-reactive and indeterminate (33% vs. 44% vs. 22%; p = 0.56), respectively. The percentage of CMV-IE1-specific NKT cells in those with clinically significant CMV infection were lower than those without infection (0.18% vs. 1.93%, p = 0.03). In multivariate analysis, neurological involvement was associated with clinically significant CMV infection (OR 7.9; 95% CI 1.5-41.9, [p = 0.015]). Conclusion: Active SLE patients with neurological involvement who received intense immunosuppression are at risk of CMV infection. Lack of CMV-specific NKT cell response tends to be associated with CMV infection. Disclosures: All Authors : No reported disclosures